Pinheirinho: dinâmica de repressão e resistência na reconstrução dogmática do conflito fundiário urbano - Ginjo, Milena de Mayo (2016)
On January 22, 2012, eight thousand people were forcibly evicted from their homes as a result of judicial decison that determined the repossession of the area. This happened in a litigation started in 2004, when the company's bankrupt estate Selecta Industry and Trade S.A. proposed the repossession against the residents of Pinheirinho occupation in São José dos Campos, São Paulo. Given these facts, the main goal of this study is to focus attention on the justice system before the conflict processing. We wanted to understand how the actors of this system influence the urban space and how was the legal mobilization of Pinheirinho actors around the judicial process. How the legal instruments were articulated to resist the repressive state? Through the dogmatic reconstruction of the land conflict, through judicial proceedings instituted from the Pinheirinho foundation in 2004, we observe how the space of the judicial process is configured in a dispute arena of social movements around the meanings of rights and the roles of the Rule of Law.